Optimal integration of shunt capacitor banks in distribution networks for assessment of techno-economic asset. (October 2018) - Dixit, Mukul; Kundu, Prasanta; Jariwala, Hitesh R.
Abstract: This article presents optimal incorporation of shunt capacitor banks in distribution feeders for the purpose of reduction of power loss, total annual expenses and voltage deviations. Additionally, it improves the voltage level, power factor and voltage stability of the network. To attain these proposed goals, a new multi-objective function has been formulated subjected to some operating constraints. This problem has been solved through Modified Gbest-guided Artificial Bee Colony (MGABC) meta-heuristic optimization technique. This proposed methodology is divided into two parts. In first part, the sensitivity buses are determined using Loss Sensitivity Factor (LSF) approach. In second, the optimization algorithm identifies the optimal buses from derived sensitive buses along with optimal size of shunt capacitors. This proposed methodology is implemented on standard 34-bus and 118-bus distribution feeders. In addition, the achieved numerical outcomes have been compared to the various intelligent approaches for showing the viability and effectiveness of the proposed approach.